2002
DOI: 10.1017/s1752756200006724
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maturity of maize silage at harvest on the performance of lactating dairy cows offered two contrasting grass silages

Abstract: Under Northern Ireland conditions, until recently, it was difficult to achieve high starch maize (greater than 200 g/kg DM) more often than one year in fifteen. However, recent developments in maize breeding and in agronomic practices, particularly the development of degradable full cover plastic mulch, have resulted in the possibility of consistently producing high starch maize. As there is considerable variability in the quality of grass silage produced on Northern Ireland dairy farms, the objective of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Improvements in intakes with inclusion of MS in GS-based diets have been demonstrated in previous studies with beef cattle (Browne et al, 2000;O'Kiely and Moloney, 2000) and with dairy cows (Phipps et al, 1995O'Mara et al, 1998;Keady et al, 2002aKeady et al, , 2003.…”
Section: Total Diet Dm and Me Intakementioning
confidence: 69%
See 1 more Smart Citation
“…Improvements in intakes with inclusion of MS in GS-based diets have been demonstrated in previous studies with beef cattle (Browne et al, 2000;O'Kiely and Moloney, 2000) and with dairy cows (Phipps et al, 1995O'Mara et al, 1998;Keady et al, 2002aKeady et al, , 2003.…”
Section: Total Diet Dm and Me Intakementioning
confidence: 69%
“…Furthermore, recent estimates indicate that production costs of maize silage (MS) can be competitive with those of grazed grass and grass silage (GS) (Keady et al, 2002b). 0301 A number of studies have reported positive effects on feed intakes when forage MS replaced GS either totally or as part of the forage base for beef cattle (McCabe et al, 1995;Browne et al, 2000;O'Kiely and Moloney, 2000;Keady and Kilpatrick, 2004) and dairy cows (Keady et al, 2002a. However, improvements in forage intake, observed in many studies, have not consistently resulted in improved levels of animal performance (O'Kiely and Moloney, 2000) such that the production, and ultimately financial, implications of incorporating MS into the diet of beef cattle is not clear.…”
Section: Introductionmentioning
confidence: 99%